Test of Learning Capability Model in Nepalese Commercial Banks - Bhandari, Dilliram (Dristikon: A Multidisciplinary Journal, 2020)
Learning and innovation are being threshold capabilities of modern organizations. Taking this into consideration, this study attempts to explore the learning orientation of organizational learning capability (OLC) and test a learning model in Nepalese commercial banks which have been operating in a highly competitive and volatile environment with strict regulatory frameworks. A descriptive research design has been followed to explore the state of OLC in Nepalese commercial banks. The population of this study comprised of all 27 commercial banks of Nepal and the sample frame for this study included 11 commercial banks, out of which, three were publicly-owned banks and eight were private sector banks. The informants of this study are the middle and top-level employees of the sample banks from both branch and corporate (head) offices. Altogether 415 questionnaires were distributed, out of these 265questionnaires were returned and finally, 245 responses were used for further analysis. Descriptive research design was followed to explore the state of OLC in Nepalese commercial banks. The development of the measurement model of OLC was achieved at two level sex placatory factor analysis (EFA) and confirmatory factor analysis (CFA). This study proposes leaning model for Nepalese commercial banks. This is expected to give the first insight into the items and constructs to build the learning capability model for enhanced organizational effectiveness. This study also showed that Nepalese commercial banks are in poor state of OLC that shows they not oriented towards learning for building their capabilities.